Pengembangan Perangkat Pembelajaran Melalui Pemecahan Masalah untuk Meningkatkan Penalaran Matematis Mahasiswa Program Studi Pendidikan Matematika Jurusan PMIPA FKIP Universitas Riau - Maimunah Maimunah; Titi Solfitri; Putri Yuanita (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2017)
Current learning and mathematical reasoning who have not been up, to be the reason to conduct research development. The desired product in this study is a learning device such as RP and LKM to improve the mathematical reasoning through problem solving. Methode used such as Plomp and quality of the products developed by Nieveen. Assessment of product is the validity (validator), practicality, and effectiveness (results limited trial). Limited trial demonstrated the practicality criteria have been met as students respond positively to the learning, structure and step sequences of learning, interest in learning, and the LKS. Effectiveness criteria have been satisfied with either minimal category, or an increase of mathematical reasoning.